Hormonal Contraceptives and Cerebral Venous Thrombosis Risk: A Systematic Review and Meta-Analysis - Amoozegar, Farnaz; Ronksley, Paul E.; Sauve, Reg; Menon, Bijoy K. (Frontiers in Neurology, 2015)
Objectives: Use of oral contraceptive pills (OCP) increases the risk of cerebral venous sinus thrombosis (CVST). Whether this risk varies by type, duration, and other forms of hormonal contraceptives is largely unknown. This systematic review and meta-analysis update the current state of knowledge. Methods: We performed a search to identify all published studies on the association between hormonal contraceptive use and risk of CVST in women aged 15–50 years. Results: Of 861 studies reviewed, 11 were included. The pooled odds of developing CVST in women aged 15–50 years taking OCPs was 7.59 times higher compared to women not taking OCPs (OR = 7.59, 95% CI 3.82–15.09). Data are insufficient to make conclusions about duration of use and other forms of hormonal contraceptives. Conclusion: Oral contraceptive pills use increases the risk of developing CVST in women of reproductive age. Future studies are required to determine if duration and type of hormonal contraceptives modify this risk.